IbM KEPADA IBU-IBU PKK RT 8 DAN RT 10 DI DESA GROBOGAN KECAMATAN JIWAN MELALUI PEMANFAATAN TAS KRESEK BEKAS MENJADI PRODUK RAJUT SEBAGAI KERAJINAN TANGAN RAMAH - Ningsih, Nuri Ati; Waraulia, Asri Musandi (Jurnal Terapan Abdimas, 2016)
This activities conductedÂ Â to overcome the problem of rubbish produced by the environment around. In this case, plastics as the main focus to be hadlled in the form of handicraff, such as bag, wallet, pencil case, and handphone case. Some purposes will be gained, they are (1) decreasing the number of rubbish produced by environment, especially plastics bag; (2) helping the housewives to increase their income by making some handicraff from plastics; (3) supporting the envirnment to be a go green area. This activities have been done in a routine workshops attended by some housewives in two group activities. The result of activities are; (1) some products from plastics , (2) positif activities done by some housewives, and (3) clean environtment/go green area.Â Keywords: rubbish, plastics bag, housewife, and go green area.